Estratégia de marketing para promoção do uso de sementes de milheto no sul do Brasil - Bohm, Marcos (2012)
The present study addresses the issue of strategic marketing planning for millet of seeds, with the ultimate goal of realizing a proposal for a strategic marketing plan, based on the variables of perceived value (4 P's) aimed at expanding the product in market. The data used in the study were obtained through extensive research, covering various areas of business, accompanied by the same directors. From the methodology, the survey began with the characterization of the company and the products and follow with the proposed strategic plan, so the first activity was to analyze the internal and external environment through the SWOT analysis, which looked at the forces, weaknesses, opportunities and threats. Based on the SWOT analysis, we developed the proposals for the marketing mix consisting of: Product: Trace and strict control throughout the production process of the TS field, selected seeds with high potential; Price: definition of price taking into account the cost-benefit to consumers, allowing a company to greater profitability, Promotion, training resellers, specialized publication in print, free distribution to consumers opinion makers; distribution: Answering larger customers with their own logistics, and customers of lower volume through a partnership with wholesale distributors.